8n+8(n+7)=-35+3n

Simple and best practice solution for 8n+8(n+7)=-35+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8n+8(n+7)=-35+3n equation:


Simplifying
8n + 8(n + 7) = -35 + 3n

Reorder the terms:
8n + 8(7 + n) = -35 + 3n
8n + (7 * 8 + n * 8) = -35 + 3n
8n + (56 + 8n) = -35 + 3n

Reorder the terms:
56 + 8n + 8n = -35 + 3n

Combine like terms: 8n + 8n = 16n
56 + 16n = -35 + 3n

Solving
56 + 16n = -35 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
56 + 16n + -3n = -35 + 3n + -3n

Combine like terms: 16n + -3n = 13n
56 + 13n = -35 + 3n + -3n

Combine like terms: 3n + -3n = 0
56 + 13n = -35 + 0
56 + 13n = -35

Add '-56' to each side of the equation.
56 + -56 + 13n = -35 + -56

Combine like terms: 56 + -56 = 0
0 + 13n = -35 + -56
13n = -35 + -56

Combine like terms: -35 + -56 = -91
13n = -91

Divide each side by '13'.
n = -7

Simplifying
n = -7

See similar equations:

| ((x^8y^-4)/(16^(4/3)))^(-1/4) | | Y=-8x^2-10x+3 | | 6X+16=2x-12 | | 142.09=6s+17.47 | | -5x+9=-4x+8-x-3 | | 14/15x=12 | | -14-v=1+2v | | 5v^2-9=81 | | 3(w-7)-3=-5(-4w+6)-5w | | 2-2y=14+4y | | 2m/7=6/21 | | -25+6x=-3(7-2x) | | 4y+9-6y=15-8y | | 5n-7=7(n-1)-2n | | 1790/0.08 | | -16t^2+124t-84=0 | | 10/13x=4 | | 1+6b+4b-4=4b+7b | | 4x^2(x^2+6xy-7y^2)= | | 5(x+2)+x=6(x+3)-4 | | -7+9x=20 | | -17=13+-10n | | X^2-8x-16=81 | | 3c+6-4c=4+2c | | 9/10x=9 | | -16t^2+88t-40=0 | | 112.07=4s+17.03 | | 4x+25=x | | 3c+6-4c=4+2x | | 15w^2-14w+3=0 | | 3(2k-7)-4=-(2k-7) | | -13=-r-6 |

Equations solver categories